The Effectiveness of Group Counseling With Self-Control Techniques to Improve Student Learning Discipline (Research on Grade X MM 3 Students Of SMK Muhammadiyah Salaman) - Wahyu Adytia, Ogan; Indianti; Eko Putro, Hijrah (Zona Education Indonesia, 2023)
This research aims to determine the effectiveness of group counseling using self-control techniques to improve learning discipline in class X Multimedia 3 SMK Muhammadiyah Salaman. The design in this research is a quasi-experimental design (Quasi Experimental Design) with the Pretest-Posttest One Group Gesign model. Research subjects were selected using purposive sampling. The sample taken was 8 students as the experimental group. The data collection methods used were learning discipline questionnaires and unstructured interviews. Test the validity of the learning discipline questionnaire instrument using the product moment formula, while the reliability test uses the Cronbach alpha formula with the help of the SPSS for Windows version 23.00 program. The analysis prerequisite tests consist of a normality test and a homogeneity test. Data analysis used parametric statistical techniques, namely the Paired Samples T-Test using the SPSS for Windows version 23.00 program. The research results show that students' learning discipline has increased after receiving group counseling with an average of 25% and the results of the Paired Samples T-test analysis with a significance value showing p=0.000. The probability results show less than 0.05, so the Ha hypothesis is accepted and Ho is rejected. Based on the research results obtained, it can be concluded that group counseling using self-control techniques is effective in improving learning discipline in class X Multimedia 3 students at SMK Muhammadiyah Salaman